2015
DOI: 10.1007/s10230-015-0349-1
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidative Precipitation of Thallium at Alkaline pH for Treatment of Mining Influenced Water

Abstract: Thallium (Tl) may exceed regulatory limits in mining-influenced water (MIW) associated with processing cadmium, copper, gold, lead, and zinc ores. It is a toxic metal that is soluble over a wide pH range, resulting in both persistence in the environment and poor removal by conventional lime precipitation. This study evaluated the effect of potassium permanganate (KMnO 4 ) at alkaline pH on Tl removal from MIW in batch experiments. The oxidation of Tl ? to Tl 3? by KMnO 4 and subsequent Tl removal was explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…This is what ultimately results in the extreme isotopic fractionation of Tl by Mn (? Fe) Davies et al 2016;Xu et al 2019) oxides, which leads to very positive isotope compositions. The Eh-pH diagram showing the strong predominance of Tl ?…”
Section: Physical and Chemical Characteristics Of Thalliummentioning
confidence: 99%
“…This is what ultimately results in the extreme isotopic fractionation of Tl by Mn (? Fe) Davies et al 2016;Xu et al 2019) oxides, which leads to very positive isotope compositions. The Eh-pH diagram showing the strong predominance of Tl ?…”
Section: Physical and Chemical Characteristics Of Thalliummentioning
confidence: 99%
“…Currently available methods for Tl removal mainly include adsorption [15][16][17][18], oxidation-reduction precipitation [19,20], solvent extraction [21], and ion exchange processes [22]. Most of these studies were conducted at a higher Tl concentration using model water [7], which is not consistent with the actual circumstances, i.e., real wastewater, where Tl concentration therein generally ranges from only a few µg/L to a few mg/L [23], while rarely exceeding 10 mg/L [24].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, further research on the treatment of wastewater with lower Tl concentration (<1 mg/L) is essential. In their recent review of Tl removal processes, Xu et al [7] highlighted that, until now, only a few studies, where strong oxidants [20,25] or advanced oxidation [19,26] methods were used, reported that the effluent Tl concentration can meet the Tl emission standards of industrial wastewater in China (5 µg/L) and of some provincial standards (2 µg/L). Therefore, it is crucial to introduce a cost-effective technology for deep purification of low Tl concentration industrial wastewater to meet the strict emission requirements and reduce the risk of Tl pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Considering its high environmental toxicity and undoubted risks to human health, Tl-bearing wastewater with Tl concentrations above 2 μg.L -1 have required being treated if discharged into surface water identified as a drinking water source [5][6][7]. Generally, Tl-bearing wastewater was treated with adsorption, oxidative precipitation, ion exchange, filtration, electrodialysis, and reverse osmosis for decontamination [7][8][9].…”
mentioning
confidence: 99%
“…Generally, Tl-bearing wastewater was treated with adsorption, oxidative precipitation, ion exchange, filtration, electrodialysis, and reverse osmosis for decontamination [7][8][9]. However, these processes were expensive and complex facilities or they led to secondary pollution [6]. For example, ion exchange was easily affected by environmental factors.…”
mentioning
confidence: 99%